Fungsi dan pentingnya identitas nasional dalam membangun jati diri bangsa indonesia dalam era globalisasi - Wulandari, Dwi Mayfah (Maliki Interdisciplinary Journal, 2025)
National identity is a fundamental element that distinguishes a nation from other nations, and in Indonesia, the motto Bhinneka Tunggal Ika, the Indonesian language, the state symbol Garuda Pancasila, as well as the diversity of cultures and traditions. However, in this era of rapid globalization, national identity faces serious challenges due to the influence of foreign cultures (acculturation), especially when considering the hedonistic lifestyle that has been adopted by some Indonesian youth, which can potentially erode local values and national identity. The statement of the function and importance of National Identity as a strengthener of the Indonesian nation in the Era of Globalization in this study aims to analyze the function and importance of national identity in building the identity of the Indonesian nation in depth. The method used in this research is a literature study with a qualitative descriptive approach to explore various aspects of national identity. The results of the study show that national identity not only acts as a unifying tool. However, it also functions as a character builder, as well as a bulwark against the influence of foreign cultures that are not in accordance with national values. Awareness and understanding of national identity is the key to strengthening the spirit of nationality and maintaining the integrity of the Unitary State of the Republic of Indonesia (NKRI). Strengthening character education and the implementation of national values in people's lives is a solution for national identity.